2019
DOI: 10.1038/s41598-019-52448-3
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Gait Analysis and Cerebrospinal Fluid Tap Test for Idiopathic Normal-pressure Hydrocephalus

Abstract: We investigated gait performance utilizing a quantitative gait analysis for 2 groups: (1) idiopathic normal-pressure hydrocephalus (INPH) patients who had a positive response to the cerebrospinal fluid tap test (CSFTT) and (2) healthy controls. The aims of the study were (1) to analyze the characteristics of gait features, (2) to characterize changes in gait parameters before and after the CSFTT, and (3) to determine whether there was any relationship between stride time and stride length variability and Front… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 50 publications
1
27
1
Order By: Relevance
“…It was reported that more than half of INPH patients (56%) experienced falls 34 . Further, we previously reported that stride time and stride length variability were increased in INPH patients relative to controls 21 . Therefore, increased gait variability may be one of the main risk factors for falls in INPH patients 21 .…”
Section: Discussionmentioning
confidence: 82%
See 4 more Smart Citations
“…It was reported that more than half of INPH patients (56%) experienced falls 34 . Further, we previously reported that stride time and stride length variability were increased in INPH patients relative to controls 21 . Therefore, increased gait variability may be one of the main risk factors for falls in INPH patients 21 .…”
Section: Discussionmentioning
confidence: 82%
“…Further, we previously reported that stride time and stride length variability were increased in INPH patients relative to controls 21 . Therefore, increased gait variability may be one of the main risk factors for falls in INPH patients 21 . We cautiously suggest that the vision-based gait analysis system has the potential to ‘bridge the gap’ between laboratory testing and clinical assessment of fall risk in INPH patients.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations